De stijl van het Stedelijk. - Huygen, Frederike; Reitsma, Lex; Premsela.org (Rotterdam : nai010 uitgevers, 2012)
The reopening of the Stedelijk Museum Amsterdam on 23 September 2012 will mean the inauguration of a spectacular new edifice as well as a new house style. The Style of the Stedelijk is the fascinating account of the Stedelijk Museum's unique relationship with graphic design and search for a new visual identity. In the documentary and the book 'The Style of the Stedelijk' filmmaker Lex Reitsma and design historian Frederike Huygen examine the long search for a new house style. The various participating designers and their proposals are presented, as well as the house style concept developed under current director Ann Goldstein by Mevis & Van Deursen, and the museum's fascinating history and unique relationship with graphic design.
boek